2005
DOI: 10.1002/pip.656
|View full text |Cite
|
Sign up to set email alerts
|

A model for the series–parallel association of photovoltaic devices

Abstract: This work presents a method to obtain the one-exponential model parameters of a series-parallel association of photovoltaic (PV) devices. From the linear expressions of the I-V characteristic in short-circuit and open-circuit zones, simple equations for association model parameters are obtained based on cell parameters. In order to validate the model, measurements have been performed in the 33 cells of a conventional PV module previously modified to have access to its cells, either individually or associated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In order to facilitate the mathematical analysis and provide an accurate numerical set of values for the first-order sensitivity a Matlab application is implemented In relation (26) the theoretical value of open-circuit voltage is obtained by using the first order sensitivity of these parameter results from relation (19), when the irradiance level changes with ∆G=400 W/m 2 and the sensitivity calculation is related to the STC conditions.…”
Section: B Theoretical Resultsmentioning
confidence: 99%
“…In order to facilitate the mathematical analysis and provide an accurate numerical set of values for the first-order sensitivity a Matlab application is implemented In relation (26) the theoretical value of open-circuit voltage is obtained by using the first order sensitivity of these parameter results from relation (19), when the irradiance level changes with ∆G=400 W/m 2 and the sensitivity calculation is related to the STC conditions.…”
Section: B Theoretical Resultsmentioning
confidence: 99%
“…In terms of studying the energy transferred from the "solar source" to PV cell the 2-terminal of the current source can be considered 1-port for the equivalent circuit, or an input port, as in [10], [11], and [12]. From this theoretically premise it is possible to consider that the input current and voltage of PV cell are I ph , respectively V d .…”
Section: New Definition Of Pv Cell Efficiencymentioning
confidence: 99%
“…The number of cells in a branch and the number of branches on a ECS Transactions, 14 (1) 529-537 (2008) module depend on the type of cell used, on the desired current-voltage-power specifications for the load and on environmental conditions. Since the output characteristic of a module resembles that of a single cell, Alonso-Garcia et al (6) suggested that Equation 1 be also used for an association of photovoltaic cells, where its parameters must be derived from a combination of the parameters of the individual cells employing the linearized equations [Eq. 2 and 3].…”
Section: The Photovoltaic Modulementioning
confidence: 99%
“…Studies of the association of photovoltaic (PV) cells contemplate several different approaches: Kirchoff rules; numerical methods, mostly based on SPICE; MPP analysis; and module-parameter extraction from individual-cell parameters (1,2,3,4,5). Alonso-Garcia et al (6) developed a simple analytical method to attain the aggregation model of either series or parallel associations of PV cells, being valid for the complete I-V range under uniform irradiation. In this paper we recur to the latter approach and propose a model for the mixed association, more commonly found in practical PV modules, where non-uniform irradiation can be considered.…”
Section: Introductionmentioning
confidence: 99%